The complications of neovaginoplasty: treatment and prophylaxis - N. D. Kuchba (Andrologiâ i Genitalʹnaâ Hirurgiâ, 2014)
The main goal of surgical treatment for patients with male type of transsexualism is restoration of male perineum organs with formation of genitals similar to feminine one. Functional and esthetic results often don’t satisfy patients and don’t provide psycho-social adaptation and even lead to suicidal attempts in some cases. Complications that are typical for one method or another have serious impact on results of the research. This article analyses vaginoplasty treatment of 103 patients with the use of variety of methods. 33 patients were diagnosed with complications at early and remote post operational period. All of the complications were sorted in two groups: general surgical (6 complications types) and specific (3 complications types). At early post operational period, 6 complications types were recorded in 21 clinical monitoring. At remote post operational period, 3 complications types were recorded in 25 clinical monitoring.Analysis of results of surgical treatment of over 100 patients with masculine gender identification disorder demonstrated advantage of neovaginoplasty method with the use of modified penile inversion and corporotomy over other methods. With the use of such methods only 8 patients developed various types of disorders. 6 patients had general surgical disorders, while 2 patients had specific disorders.Authors of this research gathered significant experience in surgical treatment of patients with masculine type of transsexualism, as well as post-operational care. As a result, this allowed to significantly lower the number of early and late stage complications.